Encyclopedia of political communication - Kaid, Lynda Lee.; Holtz-Bacha, Christina (Los Angeles, [Calif.] ; London : SAGE, 2008)
'The Encyclopedia of Political Communication' discusses the major theoretical approaches to the field, including direct and limited effects theories, agenda-setting theories, sociological theories, framing and priming theories, and other past and present conceptualisations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communication in politics -- Encyclopedias